Training of ag-extension agents and farmers on validated best-bet CSA packages for crop, forage, and small ruminant value chains to manage climate and non-climate risks in Southern and Central Highlands of Ethiopia - Ambaw, Gebermedihin; Nigussie, Abebe; Terefe, Hailu; Habtegiorgis, Kebede (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The CGIAR research program on climate change, Agriculture and food security (CCAFS) organized training on validated best-bet CSA packages for crop, forage, and small ruminant value chains to manage climate and non-climate risks in collaboration with The Alliance of Bioversity International and International Center for Tropical Agriculture, Africa RISING, ICARDA, Inter Aide, Debre Berhan University, Areka Agricultural Research Center, and Ministry of Agriculture (MoA). The training was carried out between July 15-20, 2021 in Basona Werana and July 31 – August 11, 2021, in Doyogena climate smart landscapes. The training targeted smallholder farmers, and early career experts (i.e. technicians and development agents) from the national partners including district agricultural offices, Areka agricultural research center, Debre Birhan University, and Inter Aide. A total of 443 farmers (87 female and 356 male) and 64 early career experts (8 females and 56 males) were included in the training in both climate smart landscapes. For farmers, the training was given in the local languages. The training covered the following topics: climate change and its risk and impact on agriculture, restoring Agroecology and sustainable benefits, adaptation and mitigation strategies, including soil and water management interventions, on-farm integration of highvalue agroforestry trees, animal feed/fodder, reforestation at a larger landscape scale, nutrient management, and small scale solar-based irrigation. In addition, the sustainable benefits of Agroecology and the concept of community-based breeding programs to improve small ruminant genetics were covered. Training on the use of calculators to estimate greenhouse gas emissions is given to the technicians. Farmers and technicians, development agents, and experts were trained on how to collect data within CBBP cooperatives, evaluation of cooperative breeding sires, pregnancy test, mass synchronization, artificial insemination, principle, and method of breeding ram selection, ranking, and certification, utilization of forage legumes, use of alternative feed resources, ewe flushing, fattening and on the characteristics and controlling methods of small ruminant pests and diseases.